Crustal thickness, rift-drift and potential links to key global events - Paulsen, Timothy; Deering, Chad; Sliwinski, Jakub; Chatterjee, Snehamoy; Bachmann, Olivier; Guillong, Marcel (Terra Nova, 2020)
Orogenic crustal thickening leads to increased continental elevation and runoff into the oceans, but there are fundamental uncertainties in the temporal patterns of thickening through Earth history. U-Pb age and trace element data in detrital zircons from Antarctica are consistent with recent global analyses suggesting two dominant peaks in average crustal thickness from ~2.6 to 2.0 Ga and ~0.8 to 0.5 Ga. Shifts in marine carbonate 87Sr/86Sr ratios show two primary peaks that post-date these crustal thickness peaks, suggesting significant weathering and erosion of global continental relief. Both episodes correlate well with zircon trace element and isotope proxies indicating enhanced crustal and fluid input into subduction zone magmas. Increased crustal thickness correlates with increased passive margin abundance and overlaps with snowball Earth glaciations and atmospheric oxygenation, suggesting a causal link between continental rift-drift phases and major transitions in Earth's atmospheric and oceanic evolution.